Competitiveness of developing and state trading countries - Andreas Lenel (Intereconomics, 1981)
The foreign trade policies of the industrialized countries have become increasingly complex. The states in question do not apply uniform policies to all other countries but operate different arrangements for different groups of countries. The divergencies can be easily adduced as evidence in support of charges of discrimination against one group of countries for the benefit of another group. The state trading countries for instance claim—in partial explanation of their relatively small export achievements—that the foreign trade policy of the industrialized western countries puts them at a disadvantage compared with the developing countries. Is this charge justified? The following study answers this question for the EC which is the most important market for both these groups of countries in the industrialized world.
Keywords: 330; EC Markets